Percepção de maus-tratos no domicílio pelo idoso morador no município de Juazeiro-BA - Bezerra, Maria Luiza Barros Fernandes (2010)
The Brazilian population presents an accelerated aging process. It is expected that in 2025 Brazil will be the sixth country in the world in terms of older population (IBGE, 2004). The health professional, especially those who are part of the Strategy of Family and Community Health, faces, constantly, complaints related to domestic and social violence against the elderly, and so needs to understand this phenomenon to act in their favor and ensure the quality of life of those people. The Biological Human Development Theory of Bronfenbrenner (1996) was the theoretical foundation used in this research and allowed the study of the elderly within the family micro-system, their integration within this ecological environment and so let possible the research on violence occurring at home. The aim of this study was to examine the perception of violence by the elderly and how he reacts to a situation of violence. The research, performed in Juazeiro-BA, included the participation of 10 elderly, aged between 64 and 84 years who attended the Family Health Unit and that had evidence of violence. The participants' socio-demographic information was collected from the records of the family of the elderly and complemented during the interview. From the elderly group who formed the sample, 9 were female, 6 had more than six children, 5 lived with more than four people at home, 9 were illiterate and had a religion, 6 were housewives, 10 possessed a chronic disease and 10 received up to the minimum wage: being mostly the only source of the family income. The interview had questions looking for identifying the following aspects: personal and family relationships of older people, types of violence and their perception of violence, actors of violence, reactions and strategies used by them before the situation of violence. After transcribing the interviews, was analyzed the content as proposed in Bardin (2006). The most usual forms of violence presented in the household of the elderly were psychological (90%) and neglect (100%), followed with the financial (50%) and to a lesser extent the physical (30%) and abandonment (30%). The violence was seen in the actions and circumstances experienced by them in their daily life such as drinking, mess, fighting, disagreement, brutality, disobedience, sadness and physical aggression. In relation to the violence authors, it was observed that they were, in most of the cases, the victim's children, male, and financially dependent and users of drugs and alcohol. The reaction of the elderly in situations of violence was in some cases as non-existent or in other situations so timid, fearful and weak. Some older people had reactions through pathological demonstration in front of those situations. The support of family and friends, as well as religion, was the confronting strategy used. We also observed that 8 participants did not know the Elderly Statute (2003). This study highlights the need for training of professionals who are part of the family health strategy, with regard to violence against the elderly and the articulation of a support network in order to form partnerships to combat violence. It is also suggested the inclusion of the psychologist as a team member to support professionals and deliver better care. Data on the peculiar characteristics of this group may be taken into account when formulating and implementing public policies and plans for coping with violence.